Казус Кукоцкого: [роман] / Людмила Улицкая - Улицкая Людмила Евгеньевна (АСТ, 2019)
Экземпляры: ф-4 (20200902) / Инвентарный номер: 55858 / Цена: 160.00 / Сис.шифр: Р2 / Авт.знак: У 48 / ГРНТИ: 17.82 / ББК: 84(2=411.2)